Optimization of Technological Parameter of Hot Rolling Bevel Gear Wheel based on Intermediate Frequency Induction Heating - Liu Saisai; Deng Xiaozhong; Gao Zhenshan; Fu Yunlong; Hu Chenhui (Jixie chuandong)
Based on the finite element software Deform-3D, the electromagnetic-thermal coupling numerical model of induction heating of spiral bevel gear small wheel is established. The orthogonal experimental method is used to optimize the parameters of temperature, friction coefficient, die feed speed and wheel blank speed, which affect the ear protrusion defect of small wheel. The optimum process parameters are selected as follows: blooming temperature 950 ℃, friction coefficient 0.1, feed speed 0.2 mm/s and billet speed 30 r/min. When the feed of 3 mm in the rolling process is optimized, the ratio of the ear protrusion height is 20.33%, numerical simulation is conducted to verify the optimal parameter combination, and the results are good. A reference for further rolling experiment of bevel gear wheel is provided.